2022
DOI: 10.1242/dev.200491
|View full text |Cite
|
Sign up to set email alerts
|

A low-sugar diet enhancesDrosophilabody size in males and females via sex-specific mechanisms

Abstract: In Drosophila, changes to dietary protein elicit different body size responses between the sexes. Whether these differential body size effects extend to other macronutrients remains unclear. Here, we show that lowering dietary sugar (0S diet) enhanced body size in male and female larvae. Despite an equivalent phenotypic effect between the sexes, we detected sex-specific changes to signaling pathways, transcription, and whole-body glycogen and protein. In males, the low sugar diet augmented insulin/insulin-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…Males’ metabolism was highly sensitive to raspberry medium feeding, with most of the analyzed parameters having a strong correlation with this fruit media; on the other hand, females’ metabolism differences are not as evident, with no strong correlation with a specific fruit host. These differences in metabolic responses dependent on sex were already observed in D. melanogaster fed on a low sugar diet 48 , which also appears to suggest the higher plasticity of females to adapt to different nutrient availability.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Males’ metabolism was highly sensitive to raspberry medium feeding, with most of the analyzed parameters having a strong correlation with this fruit media; on the other hand, females’ metabolism differences are not as evident, with no strong correlation with a specific fruit host. These differences in metabolic responses dependent on sex were already observed in D. melanogaster fed on a low sugar diet 48 , which also appears to suggest the higher plasticity of females to adapt to different nutrient availability.…”
Section: Discussionsupporting
confidence: 59%
“…The AKH signaling pathway was already associated with gluconeogenesis and trehaloneogenesis in D. melanogaster , with its activation linked with nutrient deficiency, especially in low carbohydrate diets 45 , 46 . Also, studies on D. melanogaster already associated an increase in foxo expression with an increase in InR expression levels under low sugar diets, due to the feedback activation of InR by FOXO 47 , 48 . Thus, besides possible overconsumption of carbohydrates to counterbalance protein intake, the high glucose levels observed in males after feeding on raspberry medium could be also associated with the mobilization of energy sources to increase glucose and trehalose levels and therefore maintain sugar homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism by which biological sex contributes to the differential T2D risk between men and women is via effects on insulin sensitivity. In humans, females show higher insulin sensitivity than males (14)(15)(16)(17)(18)(19), a trend that exists in diverse species (13,(20)(21)(22)(23)(24). Given the known association between loss of insulin sensitivity and T2D (25), this provides a simple explanation for the male-biased risk of T2D in rodents and humans.…”
Section: Introductionmentioning
confidence: 93%
“…With respect to β cell function, most data from rodent and human studies suggests glucose-stimulated insulin secretion is higher in females than in males (5,10,(13)(14)(15)(16). While male-female differences in peripheral insulin sensitivity (15,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) may contribute to these differences, sex-biased insulin secretion in humans persists in the context of equivalent insulin sensitivity between males and females (5). Whether sex differences in additional aspects of β cell gene expression and function similarly persist remains unclear, as insulin sensitivity is not routinely monitored across datasets showing sex differences in β cell biology.…”
Section: Introductionmentioning
confidence: 99%
“…One limitation of our study is that our analyses of fat-body mitochondrial metabolism and body growth relied on pooled groups of male and female larvae and did not involve an analysis of phenotypes by sex. This is a pertinent point to emphasize since studies have reported sex differences in the nutrient and metabolic regulation of larval physiology and growth (Millington et al, 2021a(Millington et al, , 2021b(Millington et al, , 2022Rideout et al, 2015;Sawala and Gould, 2017;Shingleton et al, 2017). Another limitation is that we examined how nutrient availability controls fat-body mitochondrial function and systemic physiology by comparing larvae grown on our normal lab food versus low-nutrient food (20% of our normal food), but we did not manipulate specific nutrients to see if they are important in modulating fat-body mitochondrial activity.…”
Section: Limitations Of the Studymentioning
confidence: 99%